Analisis Strategi Pemasaran Berbasis Digital dalam Meningkatkan Keunggulan Bersaing Rumah Makan Doro Tarei - Muhammad Naoval; Mulyati Mulyati; Risca Ariska Ramadhan (Lembaga Riset, Publikasi dan Konsultasi JONHARIONO, 2026)
This study investigated the digital marketing strategies implemented by Rumah Makan Doro Tarei to enhance its competitive advantage amidst intense competition in the culinary sector. The main problem was the struggle of the business to optimize digital platforms and maintain consistent promotional content to attract consumers. A qualitative approach with a case study design was utilized. Data were gathered through in-depth interviews with the owner and staff, alongside observation and documentation. The findings revealed that the restaurant actively utilized various digital platforms, including social media, communication applications, digital maps, and food delivery services, to reach wider audiences and interact directly with customers. The implementation involved basic planning, execution, and evaluation stages. Despite facing challenges such as time constraints, limited design skills, and human resource shortages, the digital marketing efforts effectively increased the customer base and brand visibility. The study concluded that consistent and interactive digital marketing significantly improved customer loyalty and strengthened the overall competitive advantage of the local culinary business.